Evaluasi Produktivitas Alata Gali Muat Untuk Mencapai Target Produksi Pengupasan Overburden 43.700 Bcm/Bulan Menggunakan Metode Overall Equipment Effectiveness (OEE) Di PT. Mineral Sukses Makmur, Site Lolo, Sumatera Baratra Bar - Diki Saputra; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2023)
PT. Mineral Sukses Makmur is a company engaged in iron ore mining with an IUP area of 73.4 Ha. Overburden stripping production target of PT. Mineral Sukses Makmur in September 2022 amounted to 43,700 bcm while the realization was by using the Caterpillar 320D (01) Excavator and Caterpillar 320D Excavator (02) loading equipment of 28,024 bcm or 64% of the production target. Production of overburden stripping did not meet the target due to obstacles that caused high loss time on the digging equipment, according to field observation data. Additional productivity research on equipment working hours is needed so that the overburden stripping production target can function properly and maximize the effective working time of the loading and unloading equipment. One of the appropriate methods used to overcome this problem is the Overall Equipment Effectiveness (OEE) method, which is a method for measuring the performance of machines or equipment used in industry by considering various production losses. After that, a Fishbone diagram is used to identify the underlying causes and effects behind the production failure of overburden stripping. From the simple linear analysis equation, a simulation can be carried out to obtain the maximum loss time limit of the working hour constraints of the loading and unloading equipment that are accurate to meet the target of overburden stripping production. Then, analysis and efforts to reduce loss time were made to achieve a total production of overburden stripping of 58,059.52 bcm/month. This means that the planned production target of 43,700 bcm/month was met and even exceeded, with the OEE value of each digger being 26%. and 22%. However, the OEE value is still relatively low compared to the standard world-class OEE value, which is 85%.